2006
DOI: 10.1590/s0101-81082006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos adversos metabólicos de antipsicóticos e estabilizadores de humor

Abstract: INTRODUÇÃO: Um aumento na incidência de obesidade e diabetes melito entre pacientes psiquiátricos foi observado ainda na década de 60, como resultado indesejável do uso de antipsicóticos. Nos anos 80 e 90, a reabilitação da clozapina, a síntese dos demais antipsicóticos atípicos e a disseminação do uso do lítio e do ácido valpróico chamaram novamente a atenção para os efeitos metabólicos desses medicamentos. Este estudo tem por objetivo revisar a literatura médica a respeito dos efeitos adversos metabólicos as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
1
11
0
10
Order By: Relevance
“…Referring to the typical (neuroleptics) and atypical (second generation antipsychotics-ASG) antipsychotics, this study shows similar findings to those found in studies examining medications belonging to these groups alone (18)(19)(20)(21). The two categories showed significant associations with overweight, possibly due to the gate locking receptor of the mix mechanism 5-HT2c beta3-adrenergic, histaminergic H1 and dopaminergic D2 (22,23).…”
Section: Discussionsupporting
confidence: 83%
“…Referring to the typical (neuroleptics) and atypical (second generation antipsychotics-ASG) antipsychotics, this study shows similar findings to those found in studies examining medications belonging to these groups alone (18)(19)(20)(21). The two categories showed significant associations with overweight, possibly due to the gate locking receptor of the mix mechanism 5-HT2c beta3-adrenergic, histaminergic H1 and dopaminergic D2 (22,23).…”
Section: Discussionsupporting
confidence: 83%
“…Além disso, a hiperatividade persistente do eixo hipotálamo-hipófise-adrenal em pacientes bipolares pode estar relacionada a elevação da pressão arterial, aumento de resistência à insulina e dislipidemia 27,28 . É importante mencionar que o uso de medicamentos psicotrópicos, particularmente os antipsicóticos atípicos, também está ligado a síndrome metabólica, aumento do apetite e preferência por alimentos doces, assim como redução da atividade física 29 . Reconhece-se também que o uso do lítio está associado ao hipotireoidismo.…”
Section: Discussionunclassified
“…18,[20][21][22] Thus, the objective of this study is to assess the prevalence of metabolic syndrome in a sample composed by inpatients from the psychiatric clinic of a general hospital in Brazil, and correlate it with the psychiatric diagnoses of the patients and with the antipsychotics and mood stabilizers used.…”
Section: 19mentioning
confidence: 99%
“…It is known that weight gain is a frequent side effect of lithium, reaching above 10 kg in 20% of patients. 18 The direct action of lithium on insulin resistance is controversial. There are studies that associate its prolonged use with the lowering of glucose tolerance.…”
mentioning
confidence: 99%